Sensuous cognition : explorations into human sentience : imagination, (e)motion and perception - Caballero, Rosario, 1963-; Díaz Vera, Javier E. (Applications of cognitive linguistics, 2013)
The main topic discussed throughout the volume is the indissoluble relationship between body, mind and culture. By emphasizing the sensuous quality of human cognition, i.e. what Howes (2003: XVII) calls ""the relation of the verbal to other 'nonverbal' (or sensual) registers of communication"", the contributions in this book revisit the notion of embodiment by paying particular attention to its sensuous dimension without losing sight of its cultural and cognitive components.